(untitled) (Research, Society and Development, 2024)
The DiGeorge Syndrome is a primary congenital immunodeficiency in which the thymus is absent or underdeveloped and is not normally hereditary. Some anomalies characterize this syndrome, the most common being heart disease, underdeveloped parathyroid glands, very characteristic facial features, cleft palates, and the absence of the thymus gland or its malformation causing several repeated infections. The purpose of this work is to report a case of a teenager with deletion of chromosome 22, showing that it is possible to complete his dental care, even with difficulty, but using conditioning techniques, and conscious sedation, and the initial method used was Tell-Show-Do. In this case, dental procedures such as restorations, primary tooth extraction, preventive measures, hygiene guidance and mainly trying to make the environment more familiar for this patient who arrived with trauma from a previous treatment. Humanized techniques were also optimized, including positive reinforcement and emotional stimulation in the patient and his family to become less anxious. It can be concluded that humanization, respect for the patient’s limits, non-pharmacological techniques, medication sedation were fundamental for the completion of treatment since adolescence, making it clear that even in the challenge of care it is possible to create a bond and complete the treatment dental.